Ethnomathematical Exploration At Home Panjalin custom in Majalengka - Kurino, Yeni Dwi; Akbar, Ady (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Ethnomathematics is a mathematical concept that exists in a culture. the presence of culturally nuanced mathematics will make a major contribution to mathematics learning. The purpose of this study was to identify and describe the mathematical objects contained in the Panjalin Traditional House and their use in learning mathematics. This research is a qualitative research with ethnographic method. The instruments used in this research are documentation, interviews and literature studies directly to the respondents. The data analysis technique was carried out by data reduction, data presentation and data analysis and data exposure. The results of the study indicate that the traditional game of marbles has ethnomathematics related to mathematical concepts including geometric concepts such as cubes, blocks, squares, rectangles, and triangles. These mathematical concepts can be used to introduce and understand the concepts of geometry and distance through local culture. Keywords: Ethnomathematics, culture, Panjalin traditional house.